Iatrogenic Menopause After Treatment for Cervical Cancer. Issue 12 (December 2016) - Moss, E.L.; Taneja, S.; Munir, F.; Kent, C.; Robinson, L.; Potdar, N.; Sarhanis, P.; McDermott, H.
Abstract: The ever-improving prognosis of women diagnosed with cervical cancer has meant that survivorship and treatment-related sequelae are being brought more into the spotlight in an attempt to try to reduce morbidity and improve women's long-term health. However, there are many issues surrounding an iatrogenic menopause in cervical cancer, a variety of potential management options and barriers to treatment. Women who have become menopausal under the age of 45 years as a result of cervical cancer are significantly less likely to start hormone replacement therapy (HRT) or continue it long term as compared with those who have undergone a surgical menopause for a benign reason. High profile media reports raising concerns about the safety of HRT use have left many women reluctant to consider HRT as a therapeutic option for menopausal symptoms and many are seeking to use complementary/alternative medicine, including non-pharmacological interventions, to alleviate symptoms. The benefits of HRT in this population have been shown to reduce these effects, although adherence to treatment regimens is a challenge due to poor compliance, which is in part due to the fear of a second malignancy. The development of non-HRT-based interventions to ameliorate menopausal symptoms and reduce the long-term health consequences are needed for women who choose not to take HRT. Highlights: Treatment for cervical cancer can result in an iatrogenic menopause. Iatrogenic menopause can be associated with long-term morbidity and mortality. HRT can reduce menopausal symptoms although compliance with treatment is a challenge. Non-HRT based interventions are needed for women who chose not to take HRT.